PENGARUH PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PENINGKATAN KEPERCAYAAN DIRI SISWA TUNANETRA KELAS V SLB A YKAB SURAKARTA - Wisnu Prasetyo; Herry Widyastono; Mahardika Supratiwi (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
This research aims to find out the effect of Jigsaw-type of cooperative learning on increasing the self-confidence of the fifth grade blind students at SLB A YKAB Surakarta. This research was a quantitative research with One Group Pretest-Posttest Design. This research was applied to all  visual impairment students of 5th grade SLB A YKAB Surakarta. Determination of the sample of this research was done with saturated sampling technique. The data collection technique in this study used a self-confidence scale based on the theory and indicators by Lauster (2003), which was carried out before treatment (pretest) and after treatment (posttest). This research used content validity testing techniques by experts as a validators, then the instruments were tested on 31 visual impairment students in the Provinces of Central Java and Yogyakarta.A total of valid items were then calculated using the Cronbach Alpha reliability technique. Treatment lasted for 8 sessions, lasting 2x30 minutes each session. The results of the Wilcoxon Signed Rank Test analysis obtained a significance value of 0.018, which indicates that the significance value  0.05 means Ho was rejected and Ha was accepted. So it could be concluded that Jigsaw Cooperative Learning had an effect on increasing the self-confidence of visual impairment students.